KAJIAN PENGGUNAAN PACKET FILTERING FIREWALL MENGGUNAKAN CISCO IP ACCESS CONTROL LIST - Imam Sutoyo; Mochamad Wahyudi (LPPM Universitas Bina Sarana Informatika, 2009)
A computer network has become a necessity for any organization implementing a computer-based information system. Hence, keeping the security aspect is important to maintain the network performance so as to provide optimum service to its users and to be up against any attacks especially when it is connected to the Internet. This paper is intended to give input to computer network administrators who implement IP Access Control List (ACL) network security system as firewall. Itdiscusses the strengths and vulnerabilities of packet filtering firewall using Cisco IP Access Control List (ACL). The findings of this study will give computer network administrators better understanding on implementing Packet filtering firewall with Cisco IP ACL and comprehending the potential security holes due to its vulnerabilities.Keywords : Vulnerabilities, Packet Filtering Firewall, Cisco IP Access Control List (ACL), Cracker